The Rural Immersion program: Developing a resident-driven residency program - Niburski, Kacper; Jawanda, Nicholas (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2025)
Implication StatementThe Rural Immersion program has been created to streamline residents to less-used remote sites, and to create resident-driven curricula. The program is suggested as a possible means to increase rural retention and benefit rural communities with longitudinal care.